1998
DOI: 10.1046/j.1365-2958.1998.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress induction of the Bacillus subtilis clpP gene encoding a homologue of the proteolytic component of the Clp protease and the involvement of ClpP and ClpX in stress tolerance

Abstract: SummaryThe Bacillus subtilis clpP gene, encoding the proteolytic component of the Clp or Ti protease, was cloned and sequenced. The amount of clpP-specific mRNA increased after heat shock, salt and ethanol stress, as well as after treatment with puromycin. Two transcriptional start sites upstream of the clpP structural gene were identified, preceded by sequences resembling the consensus sequences of promoters recognized by A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(173 citation statements)
references
References 78 publications
(126 reference statements)
8
163
0
2
Order By: Relevance
“…In this work, we identified the clpP gene of S. agalactiae and showed that its product, the serine protease ClpP, is involved in the regulation of growth at high temperatures and survival under stress conditions, including heat shock, as already shown in the case of B. subtilis (Gerth et al, 1998), L. monocytogenes (Gaillot et al, 2000) and S. pneumoniae (Chastanet et al, 2001). Consistently, in all these bacteria, the synthesis of ClpP is induced under stress conditions including heat shock (Chastanet et al, 2001;Derre et al, 1999;Gaillot et al, 2001).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In this work, we identified the clpP gene of S. agalactiae and showed that its product, the serine protease ClpP, is involved in the regulation of growth at high temperatures and survival under stress conditions, including heat shock, as already shown in the case of B. subtilis (Gerth et al, 1998), L. monocytogenes (Gaillot et al, 2000) and S. pneumoniae (Chastanet et al, 2001). Consistently, in all these bacteria, the synthesis of ClpP is induced under stress conditions including heat shock (Chastanet et al, 2001;Derre et al, 1999;Gaillot et al, 2001).…”
Section: Discussionsupporting
confidence: 69%
“…Defects in cell division as a result of mutations in the clp genes have also been observed in B. subtilis and L. monocytogenes, suggesting that proteins involved in cell morphology or cell division are controlled either directly or indirectly by the ClpXP protease complexes (Gerth et al, 1998;Nair et al, 1999). In C. crescentus, ClpXP is required in vivo for the cell-cycle-dependent degradation of the regulatory protein CtrA (Jenal & Fuchs, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Clp proteases consist of two multimeric components, an ATPase and a proteolytic component, both of which are required for proteolysis (6). In B. subtilis, three Clp ATPases (ClpC, ClpE, and ClpX) and one proteolytic component (ClpP) have been described (2,4,5,21). Therefore, knockouts of all four clp genes and the ftsH gene were tested to determine whether they conferred stability to the tagged HrcA variants.…”
Section: Vol 183 2001mentioning
confidence: 99%
“…De multiples protéines Clp ont ainsi été identifiées et classées en deux sous-familles : les protéases, notamment ClpP [17] et les Clp-ATPases, chaperons moléculaires présentant aussi une activité ATPasique [21]. La protéase ClpP est une Hsp jouant un rôle clef tant lors d'un stress qu'au cours de la croissance [7,9]. L'activité protéolytique de ClpP est modulée par son association avec des protéines de la sous-famille des Clp-ATPases.…”
Section: Introductionunclassified